Implicating bites from a leishmaniasis sand fly vector in the loss of tolerance in pemphigus - Marzouki, Soumaya (JCI Insight, 2020)
A possible etiological link between the onset of endemic pemphigus in Tunisia and bites of Phlebotomus papatasi, the vector of zoonotic cutaneous leishmaniasis, has been previously suggested. We hypothesized that the immunodominant P. papatasi salivary protein PpSP32 binds to desmogleins 1 and 3 (Dsg1 and Dsg3), triggering loss of tolerance to these pemphigus target autoantigens. Here, we show using far-Western blot that the recombinant PpSP32 protein (rPpSP32) binds to epidermal proteins with a MW of approximately 170 kDa. Coimmunoprecipitation revealed the interaction of rPpSP32 with either Dsg1 or Dsg3. A specific interaction between PpSP32 and Dsg1 and Dsg3 was further demonstrated by ELISA assays. Finally, mice immunized with rPpSP32 twice per week exhibited significantly increased levels of anti-Dsg1 and -Dsg3 antibodies from day 75 to 120. Such antibodies were specific for Dsg1 and Dsg3 and were not the result of cross-reactivity to PpSP32. In this study, we demonstrated for the first time to our knowledge a specific binding between PpSP32 and Dsg1 and Dsg3, which might underlie the triggering of anti-Dsg antibodies in patients exposed to sand fly bites. We also confirmed the development of specific anti-Dsg1 and -Dsg3 antibodies in vivo after PpSP32 immunization in mice. Collectively, our results provide evidence that environmental factors, such as the exposure to P. papatasi bites, can trigger the development of autoimmune antibodies.